Whole genome sequencing of familial isolated oesophagus atresia uncover shared structural variants - Joakim Klar; Helene Engstrand-Lilja; Khurram Maqbool; Jonas Mattisson; Lars Feuk; Niklas Dahl (BMC, 2020)
Abstract Background Oesophageal atresia (OA) is a life-threatening developmental defect characterized by a lost continuity between the upper and lower oesophagus. The most common form is a distal connection between the trachea and the oesophagus, i.e. a tracheoesophageal fistula (TEF). The condition may be part of a syndrome or occurs as an isolated feature. The recurrence risk in affected families is increased compared to the population-based incidence suggesting contributing genetic factors. Methods To gain insight into gene variants and genes associated with isolated OA we conducted whole genome sequencing on samples from three families with recurrent cases affected by congenital and isolated TEF. Results We identified a combination of single nucleotide variants (SNVs), splice site variants (SSV) and structural variants (SV) annotated to altogether 100 coding genes in the six affected individuals. Conclusion This study highlights rare SVs among candidate gene variants in our individuals with OA and provides a gene framework for further investigations of genetic factors behind this malformation.